English English - Cahyo Bagus Setiawan, Heri; Rizki Ariyanto, Sudirman; Tri Umaroh, Susi (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
This study explores the dynamics of entrepreneurship in Islamic boarding schools in the context of sharia economic empowerment, using a qualitative approach and a multiple case study design. This study compares two Islamic boarding schools with different entrepreneurial characteristics: the Mukmin Mandiri Islamic Boarding School in Sidoarjo, which focuses on coffee agribusiness with exports to Australia and Malaysia, and the Rahmatan Lil Alamain Islamic Boarding School in Nganjuk, which develops micro-enterprises based on local potential. The results show that both Islamic boarding schools implement strategic management that is adaptive to their respective contexts, with key success factors including visionary leadership based on values, integrated resource management, application of sharia economic values, and adaptability of strategies to the external environment. This study contributes to the understanding of how strategic management principles can be applied in the context of Islamic boarding schools based on sharia economics.